An Integrated Pipeline for Trio‐Rapid Genome Sequencing in Critically Ill Infants. Issue 3 (27th March 2023) - Wang, Xiao; Gan, Mingyu; Dong, Xinran; Lu, Yulan; Zhou, Wenhao
Abstract: Trio‐rapid genome sequencing (trio‐rGS) can assist the genetic diagnosis of critically ill infants given its ability to detect a broad range of pathogenic variants, as well as microbes, simultaneously with high efficiency. To achieve more comprehensive clinical diagnoses, it is essential to propose a recommended protocol in clinical practice. Here, we introduced an integrated pipeline to detect germline variants and microorganisms simultaneously from trio‐RGS in critically ill infants, which provides step‐by‐step criteria for the semi‐automatic processing procedures. With this pipeline in clinical application, only 1 ml of peripheral blood is needed for clinicians to provide both genetic and infectious causal information to a patient. The establishment and clinical practice of the method is of great significance for further mining of high‐throughput sequencing data and for assisting clinicians in promoting diagnosis efficiency and accuracy. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Experimental pipeline for rapid whole‐genome sequencing for the simultaneous detection of germline variants and microorganisms Basic Protocol 2 : Computational pipeline for rapid whole‐genome sequencing for the simultaneous detection of germline variants and microorganisms